Risk and Return: Bonds and Sukuk in Indonesia - Ahmad Rodoni; Aris Setiawan (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2016)
The aim of this research is to compare the degree of risk and return of bonds with sukuk, using several calculations magnitudes, which are, yield to maturity (YTM), Macaulay's duration, and Value at Risk (VaR). The results of this study show that there is no significant difference between the YTM bonds and the YTM of emitted sukuk. Using the Macaulay’s duration formula to evaluate the duration of bonds and sukuk, the research found out that there is no significant difference in the duration of bonds and sukuk. However, the calculation and comparison of the VaR, showed a significant differences between bonds and sukuk , likewise either the comparison of the VaR of a sample group of bonds with a sample group of sukuk using k sample test. But by testing each group of the VaR of bonds sample group and sukuk sample group,the results show no significant differences.DOI: 10.15408/aiq.v8i2.3159